The prognosis of successful introduction of plants genus Cypripedium L. (Orchidaceae) - V.G. Sobko; О.V. Reshetjuk (Інтродукція Рослин, 2003)
The prognosis of the successful introduction of plants of genus Cypripedium L. are based on systematic, phyllogenetic, geographical and ecological-cenotic analysis of the investigated taxon.